2008
DOI: 10.1111/j.1467-6494.2008.00497.x
|View full text |Cite
|
Sign up to set email alerts
|

Parents' Stories of Grandparenting Concerns in the Three‐Generational Family: Generativity, Optimism, and Forgiveness

Abstract: Adults' level of Eriksonian generativity in midlife has been shown to predict variations in parenting, but there has been less research on its relation to inter generational processes in the three-generational family. As part of a larger study, a sample of 35 Canadian mothers and fathers described a particular, salient child-rearing problem with grandparents when their first-born children were 8 years old. Descriptions were rated for severity of the problem, anger/irritation, optimism about solution, and forgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 28 publications
2
12
0
3
Order By: Relevance
“…Roberto and Stroes () found that grandparents were described by university students as important socializing agents through social value transmission, especially grandmothers, except values related to occupations and instrumental activities, where grandparents had a higher influence. Similar results have been found in more recent studies (Pratt et al ; Viguer et al ; Goodsell et al ). Also, Bengtson et al .…”
Section: Introductionsupporting
confidence: 92%
“…Roberto and Stroes () found that grandparents were described by university students as important socializing agents through social value transmission, especially grandmothers, except values related to occupations and instrumental activities, where grandparents had a higher influence. Similar results have been found in more recent studies (Pratt et al ; Viguer et al ; Goodsell et al ). Also, Bengtson et al .…”
Section: Introductionsupporting
confidence: 92%
“…The study of generativity has also expanded in recent years to include the study of three‐generation families and grandparenting. For example, generative parents have been found to be more optimistic and forgiving of grandparent behaviors that they perceive to be problematic in interacting with their young grandchildren (e.g., value conflicts among grandparents and parents, lack of time that grandparents spent with grandchildren; see Pratt, Norris, Cressman, Lawford, & Hebblethwaite, 2008). Nevertheless, little research has focused on the role of generativity in the relationship between grandparents and grandchildren.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, conflictual issues may cause stress for grandparents. When such issues arise between families, more mature parents tend to be more forgiving than younger parents (towards their own parents) and see problems as less serious (Pratt, Norris, Cressman, Lawford, & Hebblethwaite, 2008). Grandparents also play an important role in instilling in their grandchildren the family history and traditions as an important role that may not always be recognized (Turvett, 2006).…”
Section: Literature Reviewmentioning
confidence: 97%